Multimodales Marketing für Münchner Neubürger. Entwicklung, Evaluation, Ausblick. - Bamberg, Sebastian; Heller, Jochen; Heipp, Gunnar; Nallinger, Sabine (Deutscher Verkehrs-Verl., 2008)
Im Rahmen eines Pilotprojektes wurden 5000 Münchener Neubürger in einer mehrstufigen Dialogmarketingkampagne über umweltfreundliches Mobilitätsverhalten informiert und motiviert. Die Evaluationsstudie ergab bei diesen Neubürgern einen um 7,6 % höheren ÖPNV-Anteil als bei der Kontrollgruppe. Von der Stadt München und der Münchner Verkehrsgesellschaft wird deshalb beabsichtigt, künftig jeden der jährlich rund 85 000 Neubürger entsprechend zu beraten. difu

As part of a pilot scheme, a multi-stage dialogue/marketing campaign - specially devised as an experimental evaluation model - has been used to inform, and motivate, some 5,000 of Munich's new residents with regard to eco-friendly mobility. This experimental group has accounted for a 7.6 per cent higher share in OPNV traffic than existing customers, a difference that is statistically significant. The marketing campaign has been judged quite positively by Munich's new residents. The city of Munich and its transport authority have extended their successful dialogue/marketing campaign to encompass all of the 85,000 new residents per year. difu
Keywords: Öffentlicher Verkehr; ÖPNV; Verkehrsverhalten; Einwohner; Marketing; Verkehrsmittelwahl; Pilotprojekt; Zuwanderer; Mobilitätsverhalten; Verkehrsmarketing; Evaluation